An Improved Shock Factor to Evaluate the Shock Environment of Small-Sized Structures Subjected to Underwater Explosion - Wenzheng Zhang; Weikang Jiang (Shock and Vibration)
Shock factor is conventionally used to assess the effect of an underwater explosion on a target. The dimensions of some structures are much smaller than the wavelength of incident wave induced by the underwater explosion. The conventional shock factor may be excessively severe for small-sized structures because it neglects the effect of scattering; so it is necessary to study the shock factor for small objects. The coupled mode method is applied to study the scattering field surrounding the cylindrical shells. A nonlinear relation differential is derived from the impact received by the cylindrical shells and the ratio between the diameters of the shells and the wavelength of the incident wave. An improved shock factor is developed based on the fitted curve, considering the scattering effect caused by the diameters of the submerged cylindrical shells. A set of numerical simulations are carried out to validate the accuracy of the proposed approach. The results show that the cylindrical shells and spherical shells under different conditions, but with the same shock factor, have almost the same shock responses.